Proračun teorijskih performanci zrakoplova s mlaznim motorom podržan računalom - Bazijanac, Ernest; Milanović, Angela (Promet - Traffic&Transportation, 2012)
The paper deals with the description of a computer program designed for the estimate of aircraft theoretical performances. The program has primarily been designed for teaching purposes. It has been based upon one simple mathematical model, given in Fortran 5.1. and applied on PC. The results of the program are displayed in graphic and textual form. It refers to an example of the estimate. of the Cessna Citation 3 theoretical performances.